Practical Management of Patients with Diabetes Mellitus in Primary Health Care - Elodia María Rivas Alpizar; Gisela Zerquera Trujillo; Caridad Hernández Gutiérrez; Belkis Vicente Sánchez (Revista Finlay)
Diabetes mellitus is a disease of major importance for public health throughout the world. This is mainly caused by its status as one of the most common non-communicable diseases and the severity and diversity of its chronic complications. An updated literary review on the management of patients with diabetes mellitus was conducted. It includes definition, diagnosis and classification, algorithm for disease’s screening, appropriate management of a patient with diabetes mellitus in primary health care, treatment pillars and goals for metabolic control. This review is aimed at exposing practical elements when approaching a patient suffering from diabetes mellitus.